ASUHAN KEBIDANAN KOMPREHENSIF PADA NY D UMUR 31 TAHUN DI PUSKESMAS WATUMALANG - Fibrinika Tuta Setiani; Habibah Naylil Muna; Romdiyah; Nur Alfiah (Jurnal Ilmiah Kesehatan, 2025)
The aim is to provide Comprehensive Midwifery Care carried out in a COC manner. The subject in this case is Mrs. D, 31 years old, at Watumalang Health Center, from March 11, 2025 to May 4, 2025. During pregnancy, Mrs. D had a high risk due to a history of abortion. No emergencies were found in Mrs. D`s newborn baby. During postpartum, the mother experienced edema in the feet, sore nipples, and poor breast milk flow. Meanwhile, the neonate experienced 3-year-old jaundice. The mother plans to use sterile contraception. Conclusion Midwifery care provided to Mrs. D from pregnancy to contraception with the COC method can reduce the risk of complications in the mother, so that the problem can be resolved properly. The suggestion from the assessment that has been carried out is to continue to provide Midwifery Services to improve early detection and prevention of complications.